1982
DOI: 10.1017/s0022112082001608
|View full text |Cite
|
Sign up to set email alerts
|

The effects of significant viscosity variation on convective heat transport in water-saturated porous media

Abstract: Weakly nonlinear theory and finite-difference calculations are used to describe steadystate and oscillatory convective heat transport in water-saturated porous media. Two-dimensional rolls in a rectangular region are considered when the imposed temperature difference between the horizontal boundaries is as large as 200 K, corresponding to a viscosity ratio of about 6·5. The lowest-order weakly nonlinear results indicate that the variation of the Nusselt number with the ratio of the actual Rayleigh number to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 3 publications
1
49
0
Order By: Relevance
“…Gary et al [9] studied the effects of significant viscosity variation on convective heat transport in water-saturated porus media. Elbashbesy and Ibrahim [10] analyzed the flow of a viscous incompressible fluids along a heated vertical plate, taking into account the variation of the viscosity and thermal diffusivity with temperature.…”
mentioning
confidence: 99%
“…Gary et al [9] studied the effects of significant viscosity variation on convective heat transport in water-saturated porus media. Elbashbesy and Ibrahim [10] analyzed the flow of a viscous incompressible fluids along a heated vertical plate, taking into account the variation of the viscosity and thermal diffusivity with temperature.…”
mentioning
confidence: 99%
“…Molla et al [11] studied the Magnetohydrodynamic natural convection flow on a sphere with uniform heat flux in presence of heat generation. Accordingly, Gary et al [12] and Mehta and Sood [13] have concluded that when this effect is included, the flow characteristics substantially change compared to the constant viscosity case. Recently, Kafoussius and Williams [14] and Kafoussias and Rees [15] have investigated the effect of the temperature-dependent viscosity on the mixed convection flow past a vertical flat plate in the region near the leading edge using the local nonsimilarity method.…”
Section: Q ( T T )mentioning
confidence: 99%
“…Following Gray at al. [23], Mehta and Sood [24], Kafoussias and Williams [25] and Kafoussias et al [26], we assume the temperature dependent viscosity μ can be of the form…”
Section: The Governing Equationsmentioning
confidence: 99%